2008
DOI: 10.1097/olq.0b013e3181660c43
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Sexual Partner Safety

Abstract: The results of this study indicate that many individuals are relying on partner attributes and relationship characteristics when assessing the STI/HIV status of a sexual partner, and that this reliance is associated with a decreased perception of personal STI/HIV risk. Prevention campaigns need to acknowledge that people are likely to evaluate sexual partners whom they know and trust as safe. Dispelling erroneous beliefs about the ability to select safe partners is needed to promote safer sexual behavior.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
34
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 28 publications
2
34
1
Order By: Relevance
“…This is consistent with the literature supporting partner-specific factors influencing safer sex behaviors (Lansky, Thomas, & Earp, 1998; Masaro et al, 2008; Rosengard et al, 2005). In the context of decision-making about HIV prevention, partner-specific assessment may be crucial to understanding intention and ability to engage in safer sex behaviors.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This is consistent with the literature supporting partner-specific factors influencing safer sex behaviors (Lansky, Thomas, & Earp, 1998; Masaro et al, 2008; Rosengard et al, 2005). In the context of decision-making about HIV prevention, partner-specific assessment may be crucial to understanding intention and ability to engage in safer sex behaviors.…”
Section: Discussionsupporting
confidence: 92%
“…The decision to engage in or not to engage in safer sex behaviors may also be specific to a given partner or type of partner (DePesa, Eldridge, Deavers, & Cassisi, 2014). For example, many people believe that knowing or trusting a partner increases that partner’s safety (Masaro, Dahinten, Johnson, Ogilvie, & Patrick, 2008). Rosengard et al (2005) found that whether a woman views her partner as a main or casual partner may determine decision-making about safe sex.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, better protection of HIV-positive inmates’ confidentiality might increase condom use. Unsafe sex based on assumptions about partners’ HIV serostatus has been documented in other studies of MSM 32 and in other populations. 33 However, our data indicate that the custody environment provides additional information, that may lead some inmates to feel increased confidence in these assumptions.…”
Section: Discussionmentioning
confidence: 77%
“…Findings may also have varied by partner type, which was not investigated in this study. Studies have found differences in condom use by partner type (Rusch, Lampinen, Schilder, & Hogg, 2004;von Haeften, Fishbein, Daspryzk, & Montano, 2000), and individuals at risk for HIV may assess risk of infection based on partner type (Masaro, Dahinten, Johnson, Ogilvie, & Patrick, 2008).…”
Section: Discussionmentioning
confidence: 98%